Tracing the connections between international business and communicable diseases - Montiel, Ivan; Park, Junghoon; Husted, Bryan W.; Velez-Calle, Andres (Journal of International Business Studies, 2022)
We posit that international business and the emergence and spread of communicable diseases are intrinsically connected. To support our arguments, we first start with a historical timeline that traces the connections between international business and communicable diseases back to the sixth century. Second, following the epidemiology of communicable diseases, we identify two crucial transitions related to international business: the emergence of epidemics within a host country and the shift from epidemics to global pandemics. Third, we highlight international business contextual factors (host country regulatory quality, urbanization, trade barriers, global migration) and multinationals’ activities (foreign direct investment, corporate political activity, global supply chain management, international travel) that could accelerate each transition. Finally, building on public health insights, we suggest research implications for business scholars on how to integrate human health challenges into their studies and practical implications for global managers on how to help prevent the emergence and spread of communicable diseases.